Persistent Pain after Cholecystectomy, When Defined Indications for Operation are Used - Tummepalli, Siddharth P. Dubhashi* and Trinath (Journal of Experimental Sciences, 2011)
Introduction: The overall prevalence of gallstones in adults is about 10% of whom approximately 1 to 2% become symptomatic. The accurate differentiation of gallstone induced biliary colic from other abdominal disease processes is the most crucial step in the successful management of gallstone disease. Persistent pain or the so-called Ã¢â‚¬Å“Post Ã¢â‚¬â€œcholecystectomy syndromeÃ¢â‚¬Â varies in frequency between 6 and 47 percent. Aims and Objectives: To study the frequency of persistent pain after cholecystectomy, when defined indications for the operation were used. Materials and Methods: This is a prospective study carried out in 70 patients in whom the indications for cholecystectomy were defined. All patients were subjected to cholecystectomy. All the patients received a self Ã¢â‚¬â€œ administered questionnaire before cholecystectomy about specific food intolerance, acid regurgitation,Ã‚Â  heartburn, nausea, vomiting, and sensation of bloating in relation to mealsÃ‚Â  during the previous 3 months. The location of abdominal pain was noted and the intensity of pain was indicated on the visual Analogue Scale (VAS). The patients were followed up at 1,3 and 6 months after the cholecystectomy and the same symptom questionnaire was administered to the patients at every visit. Results - At one month follow up, out of 37 patients who experienced abdominal pain with typical location before surgery, 32 reported total remission of pain (86.4%) whereas out of 15 patients who had vague abdominal pain before surgery, only 3 reported relief of pain (20%). At 6 months follow up out of 22 patients with localized preoperative pain, 20 reported relief (90.0%). Out of 12 patients with vague preoperative pain, 7 patients reported relief of pain (58.3%). The average VAS score at 1 month follow up was 2.5 for patients with preoperative localized pain and 4.5 for those who presented with vague pain preoperatively. The score was 1 and 3 respectively at 6 months follow up. Conclusion: The defined indications for elective cholecystectomy along with the questionnaire indicates the frequency and location of preoperative abdominal pain are useful in minimizing the frequency of persistent pain after cholecystectomy. The frequency of persistent abdominal pain after Cholecystectomy is low in patients with preoperative typical localized pain.